Effectiveness of Child Protection Laws in Cases of Sexual Abuse of Minors - Hartaty Halim; Hery Firmansyah (Jurnal Indonesia Sosial Teknologi, 2024)
Sexual abuse of minors is a serious problem that affects children's physical, psychological, and social development. The Child Protection Law in Indonesia, which is regulated in Law No. 35 of 2014, aims to protect children from violence, including sexual abuse. However, the implementation of this law still faces various challenges, both in terms of understanding law enforcement officials and obstacles in legal procedures that are not child-friendly. This study aims to analyze the effectiveness of the implementation of the Child Protection Law in handling cases of sexual abuse of minors in Indonesia. The research method used is a normative legal research method, which focuses on laws and regulations, literature, and documents related to child protection. The results show that although this law provides a clear legal basis, the main challenges lie in the lack of understanding of law enforcement officials, legal procedures that are not sensitive to victims, and lack of coordination between related agencies. In conclusion, to increase the effectiveness of law implementation, it is necessary to conduct training for law enforcement officials, improve coordination between institutions, and empower communities and educational institutions. With these steps, it is hoped that the protection of children can be more optimal.